Comparative vibration study of a diesel engine fueled with chicken fat biodiesel - Rao, K Srinivasa; Panthangi, Ravi Kumar; Kondaiah, V. V. (International Journal of Engineering and Technology, 2018)
Biodiesel is an alternative fuel and has become more attractive now a days due to its low emissions. The biodiesel can be used in existing diesel engines directly in pure form or blending with diesel. The diesel engine physical behaviour during its working is very important. The present work involves, comparative vibrational analysis of diesel engine using conventional diesel, chicken fat biodiesel and its blends with diesel at different engine load conditions. Tests are carried on single cylinder four stroke stationery engine and vibrations are measured using vibration tester. Results of the study shows that, vibration acceleration increased with engine load for all fuel blends and also increased with chicken fat biodiesel quantity in the blend. The higher vibrations with chicken fat biodiesel are due to development of higher peak pressures during combustion of oxygenated biodiesel compared to diesel.